Bentall procedure with the CarboSeal™ and CarboSeal Valsalva™ composite conduits: long-term outcomes. (18th February 2021) - Lechiancole, Andrea; Vendramin, Igor; Sponga, Sandro; Piani, Daniela; Benedetti, Giovanni; Meneguzzi, Matteo; Ferrara, Veronica; Tullio, Annarita; Bortolotti, Uberto; Livi, Ugolino
Abstract: : OBJECTIVES: Data on the long-term results with the standard CarboSeal™ mechanical conduit used for the modified Bentall procedure are lacking as well as information on performance of the Valsalva CarboSeal™ conduit. METHODS: We have analysed 208 recipients of a standard ( n = 110) or a Valsalva ( n = 98) CarboSeal™ conduit. The median age was 60 years and 90% were males; 35 (17%) had type A aortic dissection and 65 (30%) a bicuspid aortic valve. Data were retrospectively analysed and results were compared between the 2 conduit models. RESULTS: Early mortality was 1.9%; the mean follow-up was 175 ± 95 for standard and 94 ± 51 months for Valsalva conduits ( P < 0.01). Actuarial survival was 86 ± 4%, 75 ± 6%, 59 ± 7% and 51 ± 9% at 5, 10, 15 and 20 years, respectively. There were 13 thromboembolic episodes with 3 deaths with an actuarial freedom of 98 ± 1%, 94 ± 2%, 90 ± 3% and 89 ± 4% at 5, 10, 15 and 20 years, respectively. Reoperation on the aortic root was performed in 9 patients for endocarditis ( n = 8) and pseudoaneurysm at the right coronary button ( n = 1) with an actuarial freedom of 97 ± 1%, 95 ± 2%, 92 ± 3% and 87 ± 4% at 5, 10, 15 and 20 years, respectively. There were no differences between the 2 conduit models in survival and major postoperative complications. CONCLUSIONS: The CarboSeal™ conduit has shown gratifying overall performance up to 20 years and appears a valid option for a modified Bentall operation, when a mechanical prosthesis is indicated. Both CarboSeal™ conduit models provided not statistically different overall long-term results.